Perception of the role of agricultural extension services by cassava processors in Edo State, Nigeria - Onemolease, E.A.; Ehilenboadiaye, C.O.; Omoregie, O. (ADAN JOURNAL OF AGRICULTURE, 2024)
This study assessed cassava processors perception of the role of the agricultural extension service in cassava processing in Edo State, Nigeria. Specifically, it ascertained the present role or services rendered by the agricultural extension service to cassava processors and explored the latter’s expectations or extension needs. Data were collected from 167 cassava processors in the State, and analysed using descriptive statistics, multiple regression, Friedman, and Cochran tests. The major cassava products processed were gari (95.8%) and fufu (69.5%). Cochran result (χ2 = 221.57; p<0.01) revealed that linking processors to cassava tuber producers (0.790), providing information on processing technologies (0.677), organizing trainings in processing methods (0.617) and disseminating information on storage methods (0.545) were the most significant roles presently played by the extension service in cassava processing. Friedman test result (χ2 = 122.21; p<0.05) showed the most significant extension needs of the processors included providing information on credit sources (mean rank = 6.82) and cassava processing technologies (6.67) and facilitating excursions to processing industries (6.61). Income (b=0.68) and education (b=0.69) were significantly related to the processors agricultural extension service needs in cassava processing. Major constraints faced were high diesel cost (mean = 3.80), irregular electricity (mean = 3.80), inadequate finance (mean = 3.77) and high equipment maintenance cost (mean = 3.75). To this end, processors should be linked to credit providers and exposed to trainings to manage modern processing facilities.